A Complicated Tax Filing Season (GESTIÓN Y TENDENCIAS, 2018)
The tax reforms of 2014 and 2016 had commendable objectives, but their application has created unnecessary complications for professional practice. The introduction of two tax regimes, the RAI register, the monetary correction of companies' initial contributions, and two tax rates are the elements that have contributed to this tangle, which tarnishes the work of accountants who spend hours preparing the large number of mandatory sworn statements. The information the authority requires could be satisfied by submitting a statistical form allowing the Internal Revenue Service to carry out whatever analyses it deems appropriate.